Social Representations on Singaru Folk Songs in Nepal (Patan Pragya, 2022)
This study focuses on the portrayal of social values in singaru song of Salyan, Nepal. The study answered how singaru songs represent social phenomena of people. The study utilized interpretative qualitative method; the sample songs were collected through the participatory method in various occasions and ceremonies in Salyan and analysed from the perspective of social representation theory. The study has exhibited the social and cultural experiences, love-in-unionand love-in-separation emotion, caste discrimination, pleasing and traumatic feelings and sentiments caused by poverty, village headsmen, rich cunning people and fraudsters in singaru songs; political leaders also deceive needy people through corruption and oppression in the mechanism. They establish new jimwal and mukhiya in the village, and torture people in different ways. The paper exposes the readers to societies, cultures, experiences, places and political impact to the villages Salyan. It also brings singaru folk songs to the notice of international readers.